Kajian Potensi Hasil Sisa Tanaman Pertanian sebagai Pakan Ternak Sapi Potong di Kabupaten Barru - Indrawirawan, Indrawirawan; Kusumastuti, Tri Anggraeni; Suwignyo, Bambang; Latief, M Fadhlirrahman (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study aims to calculate the potential utilization of feed from roughages and feed capacity for beef cattle in Barru Regency, South Sulawesi. Research data were obtained through surveys and secondary data from government agencies, statistical data, and other literature sources related to the research. Data analysis included calculating beef cattle population (animal unit, AU), dry matter production from roughages, and roughage carrying capacity. The results showed that dry matter (DM) production from roughages in Barru Regency was 147,878.60 tons DM. This total DM production can accommodate a beef cattle population of 75,627.41 AU. The study area can still develop the potential for additional beef cattle to reach 21,081.82 AU. Optimal utilization of roughage feed can increase the population and meet the fiber needs of beef cattle in the Barru Regency.